Safety, pharmacodynamics, and efficacy of high-versus low-dose ascorbic acid in severely burned adults - Nagel, Sarah Sophie; Radu, Christian Andreas; Kremer, Thomas; Meeß, David; Horter, Johannes; Ziegler, Benjamin; Hirche, Christoph; Schmidt, Volker-Jürgen; Kneser, Ulrich; Hundeshagen, Gabriel (Journal of burn care & research, 2020)
In sepsis and burns, ascorbic acid (AA) is hypothesized advantageous during volume resuscitation. There is uncertainty regarding its safety and dosing. This study evaluated high dose AA (HDAA: 66 mg/kg/h for 24 hours) versus low dose AA (LDAA: 3.5 g/days) administration during the first 24 hours in severely burned adults. We conducted a retrospective study comparing fluid administration before and after switching from low dose to HDAA in severely burned adults. A total of 38 adults with burns >20% TBSA, who received either HDAA or LDAA were included in this retrospective study. AA serum concentrations were quantified at 0, 24, and 72 hours postburn. HDAA impact on hemodynamics, acid-base homeostasis, acute kidney injury, vasopressor use, resuscitation fluid requirement, urinary output, and the incidence of adverse effects was evaluated; secondary clinical outcomes were analyzed. AA plasma levels were 10-fold elevated in the LDAA and 150-fold elevated in the HDAA group at 24 hours and decreased in both groups afterwards. HDAA was not associated with a significantly increased risk of any complications. A significant reduction in colloid fluid requirements was noted (LDAA: 947 ± 1722 ml/24 hours vs HDAA: 278 ± 667 ml/24 hours, P = 0.029). Other hemodynamic and resuscitation measures, as well as secondary clinical outcomes were comparable between groups. HDAA was associated with higher AA levels and lower volumes of colloids in adults with severe burns. The rate of adverse events was not significantly higher in patients treated with HDAA. Future studies should consider prolonged administration of AA.